2022
DOI: 10.1002/lary.30149
|View full text |Cite
|
Sign up to set email alerts
|

Factors Impacting Discharge Destination Following Head and Neck Microvascular Reconstruction

Abstract: Objective: Determine which variables impact postoperative discharge destination following head and neck microvascular free flap reconstruction.Study Design: Retrospective review of prospectively collected databases. Methods: Consecutive patients undergoing head and neck microvascular free flap reconstruction between January 2010 and December 2019 (n = 1972) were included. Preoperative, operative and postoperative variables were correlated with discharge destination (home, skilled nursing facility [SNF], rehabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In a recent multi‐institutional study, Sweeny et al reported risk factors associated with higher likelihood of SNF disposition, including older age, a higher comorbid burden specifically relating to cardiopulmonary or vascular disease, and a higher incidence of postoperative complications leading to SNF disposition. Interestingly, their findings revealed no differences between post‐discharge surgical complications or 30‐day readmission rates between different discharge destinations 15 . Previous studies have also shown that patient education, postoperative sequelae, coordination of care, fragmentation across care organizations, a lack of family support, and socioeconomic status are all factors that have been shown to impact a patient's ability to receive the treatment they need on time 5,6,14,16,17 .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In a recent multi‐institutional study, Sweeny et al reported risk factors associated with higher likelihood of SNF disposition, including older age, a higher comorbid burden specifically relating to cardiopulmonary or vascular disease, and a higher incidence of postoperative complications leading to SNF disposition. Interestingly, their findings revealed no differences between post‐discharge surgical complications or 30‐day readmission rates between different discharge destinations 15 . Previous studies have also shown that patient education, postoperative sequelae, coordination of care, fragmentation across care organizations, a lack of family support, and socioeconomic status are all factors that have been shown to impact a patient's ability to receive the treatment they need on time 5,6,14,16,17 .…”
Section: Discussionmentioning
confidence: 90%
“…Interestingly, their findings revealed no differences between post-discharge surgical complications or 30-day readmission rates between different discharge destinations. 15 Previous studies have also shown that patient education, postoperative sequelae, coordination of care, fragmentation across care organizations, a lack of family support, and socioeconomic status are all factors that have been shown to impact a patient's ability to receive the treatment they need on time. 5,6,14,16,17 Our patients discharged to SNF initiated adjuvant therapy later than those discharged home (70.1 vs. 59 days, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…These authors note similar disparities in the rates of discharge to home vs SNF among patients and postulate a number of potential contributing factors that include clinicians’ desire to protect—by promoting institutional postacute care—the patients they perceive to be most vulnerable to adverse discharge outcomes . Within the head and neck surgery literature, Sweeny et al recently reported that older age, undergoing longer surgical procedures (>10 hours), and having postoperative complications were all associated with discharge to SNF as opposed to discharge to home. They found no correlation with anatomic site, free-flap donor selection, or free-flap survival.…”
Section: Discussionmentioning
confidence: 93%
“…Although we did find a similar result regarding older aged patients, the focus of our study aligned more with physical therapy metrics and discharge to IPR, a concept not yet studied in the field of otolaryngology to our knowledge. Other studies have found only slight correlations between CCI and discharge to IPR or an SNF 8 . One study found that longer operative duration correlates with a higher percentage of patients being discharged to IPR or an SNF 8 .…”
Section: Discussionmentioning
confidence: 97%
“…8 One study found that longer operative duration correlates with a higher percentage of patients being discharged to IPR or an SNF. 8 This could be a valuable tool, specifically for PTOT metrics, when evaluating a patient perioperatively. Parhar et al found that patients discharged to post-acute care have significantly higher rates of multiple comorbidities, were of black ethnicity, and were male gender.…”
Section: Discussionmentioning
confidence: 99%